A home in YEG: there is a province‐city plan to end homelessness in 10 years, but many of Edmonton’s street people will believe in progress when they see it - Brown, Gabrielle (My University, 2014)
Homelessness in Edmonton is examined.
Keywords: homelessness; Edmonton